A Comparative Study of Vocabulary Learning Strategies Employed by Iranian Undergraduate and Postgraduate EFL Learners with a Focus on Motivation - Abdullah Sarani; Habib Shirzaei (Indonesian Journal of EFL and Linguistics, 2016)
Vocabulary is viewed as a major part of language proficiency as it allows learners to use four language skills: listening, speaking, reading, and writing. The present study was carried out to compare Iranian undergraduate and postgraduate EFL learners’ use of vocabulary learning strategies. After that the study tried to see if there was any difference between highly-motivated and low-motivated learners with regard to vocabulary use. Finally, it aimed at investigating the differences between the Iranian EFL male and female learners’ use of vocabulary learning strategies. A group of 150 Iranian undergraduate and postgraduate EFL learners (75 males and 75 females) both at BA and MA levels from Zahedan universities were selected randomly. The participants’ ages ranged between18 to 42. The data were obtained through two questionnaires: Taxonomy of Vocabulary Learning Strategies developed by Schmitt (1997) and Gardner’s (1985) Attitude/ Motivation Test Battery (AMTB). The findings of the study showed that there was a significant difference between undergraduate and postgraduate EFL learners’ use of vocabulary learning strategies. Also, there was a difference between highly-motivated learners and low-motivated learners’ use of vocabulary learning strategies. Moreover, the results showed that the interaction between the learners’ gender and motivation was significant. The results are theoretically and pedagogically significant for EFL teachers and applied linguists